What does the Thinking about Relationalism and Humanness in African Philosophy imply for Different Modes of Being Present in the Metaverse? - Ewuoso, Cornelius (Science & Engineering Ethics, 2024)
In this article, I interrogate whether the deployment and development of the Metaverse should take into account African values and modes of knowing to foster the uptake of this hyped technology in Africa. Specifically, I draw on the moral norms arising from the components of communal interactions and humanness in Afro-communitarianism to contend that the deployment of the Metaverse and its development ought to reflect core African moral values to foster its uptake in the region. To adequately align the Metaverse with African core values and thus foster its uptake among Africans, significant technological advancement that makes simulating genuine human experiences possible must occur. Additionally, it would be necessary for the developers and deployers to ensure that higher forms of spiritual activities can be had in the Metaverse to foster its uptake in Africa. Finally, I justify why the preceding points do not necessarily imply that the Metaverse will have a higher moral status than real life on the moral scale that can be grounded in Afro-communitarianism.